2011
DOI: 10.1007/s10195-011-0138-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic prediction in patients with hip fracture: risk factors predicting difficulties with discharge to own home

Abstract: BackgroundLittle is known about risk factors that may prevent hip fracture patients from being discharged to home. The present study was developed to investigate possible prognostic factors.Materials and methodsWe studied 345 patients with hip fracture treated at our hospital since 1997, who were living at home before the injury. There were 84 males and 261 females. Mean age at injury was 81.6 years. Fracture type was femoral neck fracture in 152 patients and trochanteric fracture in 193. Patients were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 8 publications
3
43
3
2
Order By: Relevance
“…Advanced age, dementia, a walking disability and concomitant chronic systemic diseases were previously reported to be risk factors for failure to return to the patient’s own home at discharge from hospital [7]. This is largely in concordance with our findings, although we used a more general categorisation for scoring the overall degree of comorbidities (ASA classification).…”
Section: Discussionsupporting
confidence: 88%
“…Advanced age, dementia, a walking disability and concomitant chronic systemic diseases were previously reported to be risk factors for failure to return to the patient’s own home at discharge from hospital [7]. This is largely in concordance with our findings, although we used a more general categorisation for scoring the overall degree of comorbidities (ASA classification).…”
Section: Discussionsupporting
confidence: 88%
“…The population included in the study presented advanced old age. Several studies showed that age is a factor influencing mortality [6,7] and new institutionalization [4]. In our study, age did not predict intra-hospital mortality, contrary to the observations of Eschbach el al.…”
Section: Discussioncontrasting
confidence: 84%
“…Risk factors predicting difficulties with discharge to own home are age 85, chronic systemic diseases, dementia, and walking disability before injury. 26,40 It is possible that in addition to a less complicated course, discharge destination plays a role in the observed decrease in the number of readmissions within 30 days after discharge by having closer observation on the subset of patients who are more ''at risk. ''…”
Section: Discussionmentioning
confidence: 99%
“…1 In the Netherlands, between 2000 and 2004, an average of 17 000 patients were admitted per year with a hip fracture. Based on demographic changes, the absolute number of hip fractures is expected to rise by 40.4% between 2005 and 2025. 2,3 The effects of a hip fracture are serious: 25% of patients die within the first year of the hip fracture and the risk of dying from the effects of a hip fracture rises with age.…”
Section: Introductionmentioning
confidence: 99%